FATORES CRÍTICOS DE SUCESSO NA GESTÃO DE PROJETOS: o caso de uma empresa de energia - Osório, Paulo César Felix (2012)
The study aims to identify the Critical Success Factors in the most cited theoretical studies, relating them to the effectiveness and efficiency of project management and rank in order of importance, the Critical Success Factors in the opinion of experts in project management. From the point of view of the method adopted the descriptive method, as we analyze the characteristics of a given population using the survey technique using a survey instrument (questionnaire) to collect data that will meet the objectives proposed in this dissertation. The theoretical framework identified the 27 Critical Success Factors most often cited in the literature and separated this set of variables in the attributes of effectiveness and efficiency. This set of variables was evaluated by 133 project managers who, through a questionnaire, validated the 27 Critical Success Factors for the attributes of effectiveness and efficiency, which passed through analyzes of statistical techniques. With the results of field research with experts, it was possible to structure the 27 Critical Success Factors most often cited in the literature for the management of projects in order of importance and analyze the correlations between variables. The opinion of the experts consulted in the prioritization and analysis of FCS in project management can be checked for their quality and reliability using the Cronbach alpha coefficient.